Effectiveness of Egg Stimulant® and Oodev® for Maturation of Tilapia (Oreochromis niloticus) - Andra Ramadhan PB; Munti Sarida; Yudha Trinoegraha Adiputra (Jurnal Perikanan dan Kelautan, 2021)
Lack of distribution, inbreeding depression, and environmental factors were several negative impacts on tilapia fry quality. It is needed to enhance fry quality by increasing the reproduction performance of broodstocks with nutrients and hormones by using Egg stimulant® and Oodev®. This research purposed to evaluate the maturation process with Egg stimulant and Oodev application and effective doses to increase reproduction performance of female tilapia broodstocks. This research conducted within two months at Unit Pelaksana Teknis Dinas Perikanan Budidaya Air Tawar (UPTD PBAT) Wilayah Barat Tanggamus. The research design used was a complete randomized design two factors and two levels with three replications. Control treatment (K) (Egg stimulant feed 0 g/kg and Oodev injection 0 mL/kg), P1 (Egg stimulant feed 3 g/kg), P2 (Oodev injection 0,5 mL/kg), and P3 (Egg stimulant feed 3 g/kg and Oodev injection 0,5 mL/kg) The results showed that P1, P2, and P3 treatments were not significantly different to eggs diameter, gonadal maturation level, gonadal maturation index, relative fecundity, and fertilization rate. However, Egg stimulants and Oodev have functionally enhanced reproduction performances of female tilapia broodstock. It is showed by treatments have a better result than control. The effective doses of Egg stimulant, Oodev, or combination need a longer period of research to applying in tilapia.